Analysis of sprinting activities of professional soccer players - Andrzejewski, M.; Chmura, J.; Pluta, B.; Strzelczyk, R.; Kasprzak, A. (The Journal of Strength and Conditioning Research, 2013)
The aim of the study was a detailed analysis of the sprinting activity of professional soccer players. The study involved 147 players who played in 10 matches of the 2008-09 and 2010-11 UEFA Europa League seasons. The number of performed sprints and total sprint distances covered by the players were examined using collected statistical material. Two types of sprints were distinguished based on their duration: S, short-duration sprint (below 5 seconds) and L, long-duration sprint (above 5 seconds). Additionally, sprints were classified according to their distance: 0-10, 10.1-20.0, and >20 m, respectively. The analysis of the sprinting activity of soccer players also involved their respective positions of play. The study was carried out using Amisco Pro (version. 1.0.2), one of the most comprehensive up-to-date computer systems for match analysis. The statistical analysis revealed that the mean total sprint distance covered by players (?24 km/h) amounted to 237 ± 123 m. With regard to the position of play, the forwards covered the longest sprint distance (345 ± 129 m), that is, 9% longer than midfielders (313 ± 119 m) and over 100% longer than central midfielders (167 ± 87 m). The average number of sprints performed by the soccer players was 11.2 ± 5.3. It should also be emphasized that about 90% of sprints performed by professional soccer players were shorter than 5 seconds, whereas only 10% were longer than 5 seconds. Analysis of physical loads of soccer players during matches can be useful for individualization of training of soccer players` speed capabilities. It is an essential instrument of modern planning and application of training loads.